Skills of creative thinking and mathematical communication suitable for the students of the second cycle of basic education - Al Rashedi, Salem Ahmed Saif (Journal of Educational and Psychological Sciences, 2019)
The present study aimed to prepare a list of the skills of creative thinking and mathematical communication suitable for the students of the second cycle of basic education. The current research used the descriptive approach to suit the objectives of the study. The researcher relied on identifying these skills on previous studies and research related to the current research subject. Studies and examination so that the researcher to formulate a questionnaire, and the researcher through his analysis of those studies to prepare a questionnaire skills required for both innovative thinking and sports communication, and included the identification of innovative thinking skills (The creation of innovative solutions to some engineering problems- the production of geometric shapes- the identification of steps to solve engineering problems- the discovery of new mathematical relations- the solution of mathematical problems in a non- stereotyped manner), and the skills of communication sports three main skills (reading symbols- Mathematical Representation- Mathematical Representation). The importance and relative weight and the value of Ka2 were calculated on the skills of creative thinking and mathematical communication. In light of these results, the research recommended a set of recommendations and suggestions.